The Powers of Presence : Consciousness, Myth, and Affecting Presence - Armstrong, Robert Plant (University of Pennsylvania Press, 1981)
Chiefly considering African and Upper Paleolithic work, Armstrong demonstrates that concepts of beauty, truth, and excellence are irrelevant in developing the aesthetic of a specific culture. By developing a unique aesthetic typology, he offers a reinterpretation of non-Western art that integrates human consciousness and its reification as art. More than eighty handsome photographs and drawings are included.